Perilaku Pengguna dan Informasi Hoax di Media Sosial - Dedi Rianto Rahadi (University of Merdeka Malang, 2017)
User behavior in sosial media and hoax information are an interesting phenomenon today. Social media is the most effective medium in Hoax's acceptance and dissemination of information. Various backgrounds of user behavior becomes one of the factors that make it easier for them to disseminate information without going through the verification process. Research method uses a qualitative descriptive method with research object of civitas academic environment of President University. The results show the behavior of social media users in responding Hoax information is quite diverse with a variety of user backgrounds. Users understand the Hoax information and impacts that arise after disseminating the information. The main reason the users spread the information Hoax is to influence the opinions/ attitudes of others. The other reason is to become a viral Social media users also understand that Hoax information can divide the nation. To inhibit the dissemination of hoax information, the role of government and parents is needed as well as the literacy/education of social media usage so that user behavior will be wise in responding to all information received. https://doi.org/10.26905/jmdk.v5i1.1342